The Influence of Compassionate Leadership and Psychological Empowerment on Job Satisfaction Mediated by Psychological Well-Being - Virgil, Rama; Utami, Hamidah Nayati; Riza, Muhammad Faisal (Sekolah Pascasarjana Universitas Brawijaya, 2025)
This study aims to identify and explain the influence of compassionate leadership and psychological empowerment on job satisfaction, mediated by psychological well-being. This research assists PT. Bimaruna Jaya in East Jakarta focuses on decision-making and policy development to address and manage factors that impact employee job satisfaction. A proportionate random sampling technique was employed, resulting in a sample of 69 respondents, using a quantitative approach. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the aid of SmartPLS 4 software. The results indicate that compassionate leadership and psychological empowerment have a positive and significant impact on job satisfaction, which is mediated by psychological well-being. It is recommended for PT. Bimaruna Jaya East Jakarta will implement open and transparent employee recognition to help employees feel a sense of well-being and empowerment. Keywords: Compassionate Leadership, Job Satisfaction, Psychological Empowerment, Psychological Well-Being